Analisis Strategi Store Atmospher untuk Meningkatkan Kepuasan Pelanggan pada Restoran TRRC - Elma; Ashfiyah, Shofy; Azmi, Muhamad; Silaningsih, Endang (CV ODIS, 2025)
Creating a supportive atmosphere in a restaurant requires proper planning. Studies have a goal of analysis of a u.r. agency strategy implemented to increase customer satisfaction. Studies employ qualitative descriptive methods by collecting data based on observation, interviews, and documentation. Studies show that the trrc restaurant has incorporated elements of the atmosphere stores such as interior displays, stores of layout, exterior, and interiors capable of positive effects on customer satisfaction. The trrc restaurant creates a comfortable atmosphere through restaurant design, lighting, entrances, and table arrangement. In addition, the trrc restaurant also provides live music entertainment day and night to increase the appeal for customers. The atmosphere store strategy used by the trrc restaurant proves to be effective in increasing customer satisfaction shown with positive comments from customers. Studies are expected to provide referencing to other restaurants on the basis of the build strategy store atmosphere to increase customer satisfaction.